Falls frequency in elderly outpatients - Scilla,Renata Schikanowski (2013)
OBJECTIVE: Evaluation of the frequency and characteristics of falls in older adults, in order to identify the context and possible prevention. METHODS: A questionnaire about the frequency of falls in 201 elderly outpatients of cardiology, internal medicine, endocrinology and geriatrics from Hospital Servidor Público Estadual of São Paulo was applied. The questions were about number of falls, context, consequences and habits changes after the event. RESULTS: The patients who reported fall were 83.9% with a higher number of those aged between 60 and 79 years (61.6%), predominantly women (76.5%). Those with 80 years or more, the percentage of events were 37.1% and 51.7% in men. Street is the most frequent place (40%). CONCLUSION: Data revealed the importance of implementing screening tools for fall risk as well as the development of educational and prevention activities.